A Reconsideration of the Shareholder's Remedy for Oppression in Singapore. (March 2013) - Koh, Pearlie M.C.
The statutory remedy for oppression plays an important role in minority shareholder protection in Singapore. Both the scope of its application and the court's jurisdiction to make remedial orders must necessarily be wide in order for the remedy to be effective. Nevertheless, the remedy is not without limits. Indeed, it is crucial that the boundaries of the remedy be made clear so that legitimate rule of the majority is not too often, and erroneously, equated with tyranny by the majority. This paper considers a number of issues as to the scope of the oppression remedy in Singapore through a careful analysis of Singaporean cases, and also references and contrasts the approaches adopted in other common law jurisdictions.